Pengaruh Faktor Pendidikan dan Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan melalui Motivasi Kerja - Juniar Rosalina Widyawati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine and analyze the effect of education factors and transformational leadership on employee's performance through work motivation in PT. PLN (Persero) UIT JBTB UPT Surabaya. This research is a type of quantitative research with 49 permanent employee populations of PT. PLN (Persero) UIT JBTB UPT Surabaya, all over populations, is sampled in this research. This research using Partial Least Square (PLS) as a statistic analysis with software SmartPLS 3. This research indicates that education factors have a significant positive effect on work motivation. Education factors have a significant positive effect on employee's performance. Transformational leadership has no significant effect on work motivation but a significant positive effect on employee's performance. Education factors have a significant positive effect on employee's performance through work motivation, and transformational leadership has no significant effect on employee's performance through work motivation.